Optimal selection and application analysis of multi-temporal differential interferogram series in StaMPS-based SBAS InSAR. Issue 1 (1st January 2018) - Tao, Qiuxiang; Gao, Tengfei; Hu, Leyin; Wang, Zhiwei
ABSTRACT: The optimal selection of multi-temporal differential interferogram series is an important step to monitor ground subsidence using the Stanford method for persistent scatterers (StaMPS)-based small baseline subset (SBAS) interferometric synthetic aperture radar (InSAR). Using a deformation model and its two solution methods, least squares and singular value decomposition, we present the composing mode and optimal selection of multi-temporal differential interferogram series and show that their quality and quantity affect the accuracy of monitored deformation information of SBAS InSAR. Using 29 ENVISAT ASAR images covering urban areas of Beijing, China, a different number of optimal multi-temporal differential interferogram series are formed to monitor urban ground subsidence by the StaMPS-based SBAS method. The comparison and verification of test results indicate that the quality and quantity of multi-temporal differential interferogram series substantially impact the singularity and degree of ill condition of the deformation model, locations of the selected slowly decorrelating filtered phase (SDFP) pixels, and monitored annual mean subsidence velocities. The suitable number of multi-temporal differential interferogram series under the optimal quality is 1–2 for a month in urban ground subsidence monitoring using StaMPS-based SBAS InSAR, a higher quantity of differential interferograms of the optimal quality is not always better.